PENJUALAN SEPATU MEREK ‘NIKE’ DENGAN METODE AUTOREGRESSIVE INTREGATED MOVING AVERAGE (ARIMA) - Rizal Ripal Rifana; Wellie Sulistijanti (Universitas Muhammadiyah Semarang, 2017)
Sales are the prevalent income in the company and are the gross amount that is levied on the customer for goods and services, In the global trading era. Therole of Industry becomes very important, especially in maintaining fair businesscompetition. The data used is from Kavernosa Sport Shop from 2012 until 2016.ARIMA method is a model formation approach that is strong enough for timeseries analysis. In this analysis we get the best model to predict the ARIMAmodel (0,0,1) With model equation: √ (Y_t) = 32,8 + e_t + 0,4153e_ (t-1).From the equation model can be predicted that the highest number of salesoccurred in January in 2017 with a prediction of sales of as many as 45 pairs ofshoes.Keywords: Toko Kavernosa Sport Majalengka West Java, Model Shoes Brand 'Nike', ARIMA.